Keratometric changes after pterygium excision - Punjabi, Sharda; Kachhwaha, Appurv (International Journal of Research in Medical Sciences, 2020)
Background: A pterygium is a wing-shaped growth of conjunctiva and fibrovascular tissue on the superficial cornea. The pathogenesis of pterygia is strongly correlated with UV light exposure and environmental factors. The prevalence of pterygia increases steadily with proximity to the equator, and the condition is more common in men than women. It is well established fact that before entering the optical zone pterygium causes flattening of the cornea in horizontal meridian with the more normal side of the cornea usually temporally, resulting in with-the-rule astigmatism. Methods: The study included 80 patients of primary pterygium who underwent pterygium excision with conjunctival autograft adhered by autologous blood surgery. After performing routine ocular examination which includes visual acuity without and with pinhole and pre-operative keratomery was assessed by autokeratorefractometer. Repeat examination was performed after 6 weeks of surgery. Patients with recurrent pterygium, pseudo-pterygium, and history of previous ocular surgery were excluded. Results: The pre‑ and postoperative corneal astigmatism were compared after 6 weeks of surgery. The changes in corneal astigmatism were statistically significant p value <0.001. The preoperative mean corneal astigmatism of 3.41 D was reduced to 1.59 D (p value <0.001) 6 weeks after surgery, but maximum change in astigmatism was seen in Grade IV >Grade III >Grade II >Grade I. Conclusions: Primary pterygium of all grades treated with well accepted technique pterygium excision with conjunctival autograft with autologous blood gives promising results in terms of improvement in corneal astigmatism and hence visual acuity as well.